A Comparison between ‘Landscape’ and ‘Planning’ Approaches in Improving the Quality of Residence in Iran’s Mehr Housing - Sina Naseri; Seyed Amir Mansouri; Nasser Barati (منظر)
Mehr Housing now deals with a serious quality of residence, which is rooted in its planning system. The housing planning approach in Iran- the custodial approach- that emerged in the frame of a comprehensive plan influenced by the modernism movement in Europe is the reason for this crisis due to its specific attitude towards the space and atomist worldview. On the contrary, the landscape approach with its “holistic” attitude considers the improvement of residence quality depending on a system of space that guarantees the quality improvement in the frame of dual perceptual-physical criteria. This study aims to compare those components that affect the quality of residence within two “planning” and “landscape” approaches and asks what kind of relationship exists between components affecting the quality of residence within two landscape and planning approaches at different levels in Iran.  The purpose of this study is to achieve a strategy to improve the quality of residence in Mehr Housing through a comparative analysis of the theoretical foundations of “planning approach” as the custodial approach of Mehr Housing and the landscape approach. The research method of this study is qualitative based on the theoretical analysis of two landscape and planning approaches. The comparison between components affecting the quality of residence in these two approaches was made through logical reasoning. The assessment of data obtained from other studies was done by comparing them with previous components and comparison between them. Due to its sectoral and partial view on some components of quality in the residence environment, the “planning approach” could not guarantee the quality of the environment despite the importance of these components. This is the incident that has responded to the different needs of occupants by improving the quality of residence within the landscape approach in the frame of “spatial arrangement” and creating a “whole” that is simultaneously perceptual and functional. Hence, it is possible to revive the potential social capital in the Mehr Housing Project by “modifying” the conditions of the environment with an idealistic attitude- adopting a landscape approach.